2015
DOI: 10.1186/s40478-015-0185-3
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated α-synuclein in Parkinson’s disease: correlation depends on disease severity

Abstract: Introductionα-Synuclein (α-syn) is a key protein in Parkinson’s disease (PD), and one of its phosphorylated forms, pS129, is higher in PD patients than healthy controls. However, few studies have examined its levels in longitudinally collected cerebrospinal fluid (CSF) or in preclinical cases. In this study, CSF and clinical data were contributed by >300 subjects from three cohorts (the longitudinal DATATOP cohort, a large cross-sectional cohort, and a cohort of LRRK2 mutation carriers).ResultsConsistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 37 publications
3
89
0
1
Order By: Relevance
“…For instance, several studies observed increased Ser 129 P-␣Syn concentrations in CSF of PD patients (48,49). However, the measurement of the C-terminal peptide of ␣Syn (␣Syn103-140) was not possible in the present MRM as discussed above.…”
Section: Investigation Of Synuclein Origin and Hemolysis As Confoundingmentioning
confidence: 87%
See 1 more Smart Citation
“…For instance, several studies observed increased Ser 129 P-␣Syn concentrations in CSF of PD patients (48,49). However, the measurement of the C-terminal peptide of ␣Syn (␣Syn103-140) was not possible in the present MRM as discussed above.…”
Section: Investigation Of Synuclein Origin and Hemolysis As Confoundingmentioning
confidence: 87%
“…There was no specific pattern of the peptides for synucleinopathies and atypical parkinsonian syndromes. However, the determination of specific PTMs might be more sensitive as has been shown for Ser 129 P-␣Syn (48,49) and should be the focus of future mass spectrometric improvements for the characterizations of ␣Syn in CSF. This is the first study presenting quantitative data on ␤Syn and ␥Syn in CSF.…”
Section: Investigation Of Synuclein Origin and Hemolysis As Confoundingmentioning
confidence: 99%
“…Importantly, most α-syn present in LBs is highly phosphorylated, especially at serine 129 (pS129) [15, 2022], which is thought to alter aggregation and toxicity of α-syn[23, 24]. Notably, the CSF pS129 was significantly higher in PD patients than in healthy controls, and correlated with PD severity[16, 25], suggesting it may serve as a marker of PD pathology independently of total α-syn, which tends to be lower in the CSF of PD patients[18, 2629]. However, the roles of these biomarkers in AD have not yet been completely probed, particularly considering pS129 in large, longitudinal cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pSyn inclusions were also detected in the PNS which might also serve as a useful diagnostic test for PD and related synucleinopathies. Work from two independent groups on skin biopsies showed that the majority of PD patients had accumulation of pSyn in small and large nerve fibers, while no signal was detected in healthy controls and in MSA or essential tremor control subjects [133,134]. This cutaneous pathology was correlated with the progression of disease symptoms suggesting the use of this peripheral marker as a biomarker for the disease [135].…”
Section: Psyn In Human Fluids and Pns Of Synucleinopathiesmentioning
confidence: 97%